Redefinition of Feedback in Corporate Communication Management and Target Group Relations: A Literature Review - (:unkn) unknown (ISTANBUL UNIV, FAC COMMUNICATION, 2019)
Limitations of time and place during the communication process have been removed with the advent of new communication technologies, and the target groups that used to have a passive role as the receiver of a message in communication conducted with the traditional communication tools have come to have an active role in the communication activities through the new communication media. In this context, the use of feedback which enables a two-way communication is of significance in today's conditions, in which the concept of relationship and two-way communication has come forth and gained significance. In the approach of institutional communication management, organisations are, therefore, required to establish a two-way communication with their target groups having different characteristics so as to create positive relationships, based on mutual understanding, dialogue, tolerance, good intention and trust. It has been determined that the concept of feedback, which is analyzed by the document examination method in Turkish and foreign literature, is usually defined as a reply and respond in Turkish literature reviews but this definition does not suffice in foreign literature reviews, so the aim in the present study is to redefine and conceptualize this concept by categorizing it according to its usage. For this reason, types, characteristics and limitations of feedback make up the basic categories of this study. It has been concluded upon the analysis of approximately fifty documents examined on the basis of these categories that institutions use reactional, structural and indefinite feedback, that they can be deaf to their target masses and that they even use interactive social media instruments in one-way communication.
Keywords: Feedback; two-way communication; one-way communication; corporate communication; target group